2017
DOI: 10.4317/jced.54441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lack of primary stability in the survival of dental implants

Abstract: BackgroundThe survival of dental implants has been linked to primary stability. The aim of this study is to analyse the factors that influence the survival of dental implants placed without primary stability.Material and MethodsA cohort study of implants placed without primary stability was carried out between September 2011 and July 2016. All cases with registered information on the patient and surgical intervention were used. Cases that did not have a 12-month follow-up after implant placement were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Although there was little information about the primary stability on the surgical record, we should consider the importance of initial stability for successful osseointegration. 32,33 However, turning implants along with a cover screw connection during the 1-stage SFALW ultimately showed successful osseointegration with long-term survival in this study, supporting the study by Cobo-Vázquez et al 34 Therefore, providing an unimpeded, adequate healing time and a less-invasive surgical protocol were suggested. It has been reported that implant fixture displaced into the sinus cavity during the simultaneous 1-staged surgery in spite of no report in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Although there was little information about the primary stability on the surgical record, we should consider the importance of initial stability for successful osseointegration. 32,33 However, turning implants along with a cover screw connection during the 1-stage SFALW ultimately showed successful osseointegration with long-term survival in this study, supporting the study by Cobo-Vázquez et al 34 Therefore, providing an unimpeded, adequate healing time and a less-invasive surgical protocol were suggested. It has been reported that implant fixture displaced into the sinus cavity during the simultaneous 1-staged surgery in spite of no report in this study.…”
Section: Discussionsupporting
confidence: 85%
“…In 2005, Park and Wang presented their accepted classifications and treatments of various reversible complications commonly encountered during routine implant-related procedures [12]. Several studies were conducted based on Park and Wang's classification to evaluate these complications; it was concluded that careful clinical and radiographic examination of each case, accurate planning of procedures, the use of proper surgical techniques and appropriate instruments, and the correct management of healing and osseointegration all combine to prevent such events [53][54][55][56][57]. In our study, 22.22% of participants expressed poor knowledge regarding these complications, which may be explained by the unfamiliarity of this type of reversible complication classification among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The first prerequisite for the success of dental implantation is represented by achieving sufficient primary stability. This is defined as the absence of mobility of the implant after insertion and is dependent upon mechanical engagement of the fixture with the surrounding bone [ 9 , 10 , 11 ]. During bone healing, insufficient primary stability can cause excessive micromotion (>50–100 µm) at the bone–implant interface.…”
Section: Introductionmentioning
confidence: 99%